Mental Imagery in Early Psychosis - Auvinen-Lintunen Laura; Ilonen Tuula; Kieseppä Tuula; Suvisaari Jaana; Lindgren Maija (SAGE Publications Ltd, 2025)
Dysfunction in mental imagery may contribute to the development of mental disorders. We studied the vividness and controllability of mental imagery in a sample of 42 individuals with recent-onset psychosis, using a cross sectional design. Contrary to earlier studies, the claim that mental imagery is enhanced and the controllability weak in psychotic disorder was not supported. Especially the negative and affective symptoms associated with low vividness, and the stronger the symptoms the patients had, the less vivid was their imagery. Anxiety and self-neglect were the best predictors of low vividness. Only an elevated mood associated with higher vividness. The cognitive performance of the participants did not associate significantly with imagery. Surprisingly, organic modality was reported to be the most vivid modality, whereas visual imagery was the least vivid. Understanding the role of mental imagery in early psychosis may help us to understand and treat these disorders better.